Strategies that students apply after finishing the English advanced subjects at the Foreign Language Department of The University of El Salvador. - Guardado Oliva, Viqui Janette; Mercado de Pineda, Sandra Lisseth; González Orellana, Iris Mariana (2024)
Learning English as a foreign language is very important for different circumstances, necessities, and goals. Nowadays in El Salvador, the education has adopted a new system in which the English Language is not an option. On the contrary, it has been taken as a priority in the new century as well as in the culture has had an impact for using some expressions in this language. At the same time some of the circumstances and necessities are the demanding of new jobs that the globalization implies and there are opportunities for people to increase their incomes; to have access to the world of information that most of the time is in the English language and even to use technology also makes people get more interested in acquiring this language. To be successful in this process of learning will depend on the type of the activities chosen by the learners.